2019
DOI: 10.3390/cancers11030300
|View full text |Cite
|
Sign up to set email alerts
|

Association of miR-34a Expression with Quality of Life of Glioblastoma Patients: A Prospective Study

Abstract: MiR-34a acts as tumor-suppressor by targeting many oncogenes related to proliferation, apoptosis, and invasion of gliomas. We studied the relationships between health-related quality of life (HRQOL), depression, and miR-34a expression status in patients with newly diagnosed glioblastoma (GBM). A comprehensive HRQOL assessment was completed by 38 patients with glioblastoma prior to surgical resection and included the European Organization for Research and Treatment of Cancer (EORTC) questionnaire for cancer pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…Similar studies were carried out by S. Kay et al, who revealed changes of matrix metalloproteinase levels in idiopathic pulmonary fibrosis patients with different HRQOL scores [ 34 ], and by J. Hu et al, whose work linked serum miR-206 levels to the quality of life of Duchenne muscular dystrophy patients [ 35 ]. Besides our previous work on miR-34a [ 36 ], brain cancer patients’ quality of life and its association with circulating biomarkers have only been investigated by A. Bunevicius et al, whose study suggests the importance of free triiodothyronine and thyroid stimulating hormone levels [ 37 ]. All of this research indicates the possibility of patients’ quality of life prediction in various diseases and invites us to look at biomarkers from a patients’ psychological and functional point of view.…”
Section: Discussionmentioning
confidence: 99%
“…Similar studies were carried out by S. Kay et al, who revealed changes of matrix metalloproteinase levels in idiopathic pulmonary fibrosis patients with different HRQOL scores [ 34 ], and by J. Hu et al, whose work linked serum miR-206 levels to the quality of life of Duchenne muscular dystrophy patients [ 35 ]. Besides our previous work on miR-34a [ 36 ], brain cancer patients’ quality of life and its association with circulating biomarkers have only been investigated by A. Bunevicius et al, whose study suggests the importance of free triiodothyronine and thyroid stimulating hormone levels [ 37 ]. All of this research indicates the possibility of patients’ quality of life prediction in various diseases and invites us to look at biomarkers from a patients’ psychological and functional point of view.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it might be that relationships were lost due to the heterogeneity of the sample regarding tumor locations and other clinical characteristics. However, previous findings by our team group showed that miR-34a or miR-181b / d expression levels were related to patients’ functioning and tumor-related symptoms [ 41 , 42 ]. Therefore, we believe that current findings support the idea that levels of miR-181a expression might be valuable not only in predicting longer survival but also in better general functioning.…”
Section: Discussionmentioning
confidence: 94%
“…MiR-34a (hsa-mir-34a-5p) targets many oncogenes associated with proliferation, apoptosis, and glioma invasion and so have been characterized as a tumor suppressor. Moreover, it is proposed as a predictive miRNA, lower level of which associated with worse physical functioning, higher tumor volume, greater depressive symptom severity of GBM patients and the lower Karnofsky performance index [ 77 ]. Several studies have shown the suppressive role of miR-381 (hsa-miR-381-3p) in cell metastasis and EMT in glioblastoma due to the suppression of LEF1 expression.…”
Section: Discussionmentioning
confidence: 99%